Formation, Development, and Cross-Species Interactions in Biofilms - Luo, Aihua; Wang, Fang; Sun, Degang; Liu, Xueyu; Xin, Bingchang (Frontiers in Microbiology, 2022)
Biofilms, which are essential vectors of bacterial survival, protect microbes from antibiotics and host immune attack and are one of the leading causes that maintain drug-resistant chronic infections. In nature, compared with monomicrobial biofilms, polymicrobial biofilms composed of multispecies bacteria predominate, which means that it is significant to explore the interactions between microorganisms from different kingdoms, species, and strains. Cross-microbial interactions exist during biofilm development, either synergistically or antagonistically. Although research into cross-species biofilms remains at an early stage, in this review, the important mechanisms that are involved in biofilm formation are delineated. Then, recent studies that investigated cross-species cooperation or synergy, competition or antagonism in biofilms, and various components that mediate those interactions will be elaborated. To determine approaches that minimize the harmful effects of biofilms, it is important to understand the interactions between microbial species. The knowledge gained from these investigations has the potential to guide studies into microbial sociality in natural settings and to help in the design of new medicines and therapies to treat bacterial infections.